2017
DOI: 10.4013/sdrj.2017.102.03
|View full text |Cite
|
Sign up to set email alerts
|

An approximation to the design process as a dynamic capability in manufacturing small and medium enterprises: A multiple case study

Abstract: This is an open access article distributed under the terms of the Creative Commons Attribution 4.0 International (CC BY 4.0), which permits reproduction, adaptation, and distribution provided the original author and source are credited. AbstractThis research identifies the particularities of the industrial design process in 18 manufacturing small and medium enterprises (SMEs) in the central region of Venezuela. To achieve this result, an investigation of the current status of the situation was done with the pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…"Businesses started by designers have created billions of dollars of value and are raising billions of dollars in capital, and VC firms increasingly see the importance of design" (Maeda, 2015, p, 10) The value of design has been heralded in many tech businesses and the venture capital companies (Stamm, 2004;Maeda, 2016: Kim et al, 2017, and design is viewed widely as a key role to providing a strategic competitiveness in new product development (NPD) and organizational growth (Roy and Riedel, 1997;Borja de Mozota, 2002;Cañizares and Atondo, 2017). Design in Tech (Maeda, 2015) has reported that 36% of the top 25 funded start-ups since 2013 were co-founded by designers, such as Airbnb, Pinterest, Github and Slack.…”
Section: Introductionmentioning
confidence: 99%
“…"Businesses started by designers have created billions of dollars of value and are raising billions of dollars in capital, and VC firms increasingly see the importance of design" (Maeda, 2015, p, 10) The value of design has been heralded in many tech businesses and the venture capital companies (Stamm, 2004;Maeda, 2016: Kim et al, 2017, and design is viewed widely as a key role to providing a strategic competitiveness in new product development (NPD) and organizational growth (Roy and Riedel, 1997;Borja de Mozota, 2002;Cañizares and Atondo, 2017). Design in Tech (Maeda, 2015) has reported that 36% of the top 25 funded start-ups since 2013 were co-founded by designers, such as Airbnb, Pinterest, Github and Slack.…”
Section: Introductionmentioning
confidence: 99%